711. Exebacase (Lysin CF-301) Activity Against Staphylococcus aureus (S. aureus) Isolates From Bacteremic Patients Enrolled in a Phase 2 Study (CF-301-102) - Anastasiou, Diane; Cassino, Cara; Schuch, Raymond (Open forum infectious diseases, 2019)
Background Exebacase (CF-301) is a novel, recombinantly-produced, bacteriophage-derived lysin (cell wall hydrolase) which is the first lysin to report Phase 2 (Ph2) results which demonstrated 42.8% higher clinical responder rates with a single dose of exebacase used in addition to standard of care antibiotics (SOC) vs. SOC alone for the treatment of methicillin-resistant S. aureus (MRSA) bacteremia including endocarditis. We examined exebacase activity by broth microdilution (BMD) against baseline methicillin-sensitive S. aureus (MSSA) and MRSA isolates from each of the 116 participants in the recently complete exebacase”first in-patient’ Ph2 study (NCT03163446). Methods Patients with complicated bacteremia or endocarditis caused by S. aureus were enrolled into Study CF-301-102 at study centers in the United States, EU, Latin America, Israel, and Russia from 2017 and 2018. Baseline isolates from blood cultures were collected prior to administration of exebacase. Exebacase MICs against 117 isolates of MSSA (n = 74) and MRSA (n = 43) were determined at a central laboratory using a modified BMD approved by the CLSI for exebacase AST. Results The exebacase MICs of baseline patient isolates from the Ph2 study ranged from 0.125 – 2 µg/mL and the MIC50/90 values for all MSSA and MRSA isolates were 0.5/1 µg/mL. Exebacase MICs reported in a recent surveillance study were similar, with MIC50/90 values of 0.5/1 µg/mL. Of the 6 total subjects with EXE MICs of 2, 3 were clinical responders, 2 were indeterminate (not available for assessment), and 1 was a clinical nonresponder at Day 14. Conclusion Exebacase was highly active against all baseline S. aureus isolates from blood cultures obtained from bacteremic patients enrolled in the Ph2 study. Based on data from previously presented exposure target attainment animal studies, PK/PD modeling and preliminary nonclinical breakpoint assessments, we expected that strains with MIC values of ≤2 µg/mL will have been susceptible to the Ph2 clinical exebacase dose determined based on target attainment studies under study in Ph2. Disclosures All authors: No reported disclosures.